The Correlation Between Vocabulary Mastery Towards Employees’english Speaking Skill at Obstetric and Gynecology Polyclinic in Hermina Grandwisata Hospital - Okfida Yani Syaf; Diah Putri Permata Dewi (Eduvest - Journal of Universal Studies, 2021)
The research aims to analyze the correlation between vocabulary mastery towards employees’ speaking English skill. The research conducted at obstetric and gynecology polyclinic in Hermina Grandwisata Hospital. The research used quantitative research which used correlational technique design. The researcher takes 32 employees for the sample and gives test with 30 questions for English vocabulary and speaking test consist of multiple choice and oral test. The data are analyzed using by SPSS version 2.2. Based on the result of the study, it can be concluded that there is a significant effect of vocabulary mastery towards employees’ English speaking skill at obstetric and gynecology polyclinic in Hermina Grandwisata Hospital. This is evidenced by the acquisition of the results of the significant 0,000 < 0,05 and T Value = 2.824. It shows that T table is 1,697 < T value, so it can be concluded that (Ho) is rejected and (Ha) is accepted. It means that there is a correlation between vocabulary mastery (X) toward English speaking skill (Y).